MENINGKATAN KREATIVITAS SENI MELALUI PERMAINAN BAK PASIR UNTUK ANAK KELOMPOK A DI RA AL-ISHLAH KALIPARE-MALANG - Laila, Rima Azizatul; Nuryahati (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2019)
The increased children's creativity begins with activities that are easily carried out in accordance with the level of difficulty gradually. This study aims to describe the development of children's artistic creativity through sandbox games in group A children in RA Al-Ishlah Kalipare and to describe the application of sandbox games that enhance artistic creativity in group A children in RA Al-Ishlah Kalipare. The classroom action research method (Action Research) applies two cycles. Data collection techniques include interviews, observation and documentation. The results of the study in the first cycle showed that children's artistic creativity has increased after taking action with a percentage of 37.49%. However, the increase in children's creativity has not yet reached the expected success indicator so that it needs to be improved in the second cycle with a percentage of 85.71% an increase including a percentage of 48.22% including high criteria. this research can be concluded that the process of children's creativity through sandbox games is very suitable for use in the process of early childhood learning.